“I Buy Paraffin So He Can Read in the Evening” – A Study from Kenya about Parental Involvement in School - Spernes, Kari (International Journal about Parents in Education, 2023)
The present paper investigates parental involvement in a rural primary school in Kenya. Qualitative interviews have been used to gather information from ten parents, a class teacher and a head teacher. The aim of the case study is to find out how – if at all – parents are involved in their children’s education, and how important parents’ background and involvement in school activities are for their children’s results. It is also interested in determining whether the school-home relationship in rural Kenya may provide new knowledge to the relationship between minority parents and schools in western countries. The findings of the study indicate no shared responsibility between parents and school; the school is solely responsible for students’ education. Normally, parents’ responsibility is limited to providing economic resources: buying school uniforms, books and other necessities. Where the mother tongue is not a school language, some parents also prepare their children for school by code-switching at home: using both the school language and the mother tongue. There is hardly any relationship to be found between parents’ involvement and students’ results. The findings from the study may provide new knowledge about minority parents’ involvement in school in western education.